2014
DOI: 10.1589/jpts.26.1701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Home Exercise on Physical Function and Activity in Home Care Patients with Parkinson’s Disease

Abstract: [Purpose] The aim of this study was to clarify the effects of guidance in home exercise on physical function and the amount of activity in home care patients with Parkinson’s disease (PD). [Subjects and Methods] A 2-month home exercise intervention consisting of self-administered exercise by patients (self-exercise) and home visit exercise therapy guided by a physical therapist (home visit exercise) was conducted in 10 home care patients with PD to compare changes in physical function, activities of daily livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Parkinson’s disease (PD) is a progressive neuromuscular disorder found most commonly among older adults; however, its progression is relatively slow 1 ) . Thus, it is important to help maintain functional abilities related to independent living through rehabilitation 2 , 3 , 4 , 5 , 6 , 7 , 8 ) . Quality of life (QOL) also plays an important role in independent living.…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson’s disease (PD) is a progressive neuromuscular disorder found most commonly among older adults; however, its progression is relatively slow 1 ) . Thus, it is important to help maintain functional abilities related to independent living through rehabilitation 2 , 3 , 4 , 5 , 6 , 7 , 8 ) . Quality of life (QOL) also plays an important role in independent living.…”
Section: Introductionmentioning
confidence: 99%
“…The first study 15 ) was a RCT, attempting to verify the aerobic training (AET) effect and the cognitive-behavioural therapy (CBT) effect on chronic fatigue of FSHD patients which had already been theoretically proposed in the FACTS-2 protocol 18 ) . The authors collected 57 patients affected by FSHD from different Dutch study centres, and randomly divided them into three groups: an AET group, a CBT group, and a group which continued with traditional treatments.…”
Section: Resultsmentioning
confidence: 99%
“…The third study considered 17 ) was a trial reported only in academic databases concerning a domestic rehabilitation treatment for FSHD patients. Domestic physiotherapy has yielded positive results in many neurological 18 , 19 ) and orthopaedic 20 ) pathologies. In the study 17 ) , 16 patients performed exercise for three weeks (to be cyclically repeated), but the exercises prescribed weren’t described.…”
Section: Resultsmentioning
confidence: 99%
“…24,57,66,94 This suggests that giving patients the tools to success starts with early implementation of exercise programs. Early referral to physical or occupational therapy may play a role in improving exercise knowledge, decreasing fear of falling with exercise, and setting up patients with home programs 95 that may limit monetary or transportation barriers. The literature in itself has not documented the translation of physical therapy to home exercise, but guidance in exercise therapy and self-exercise will attempt to solve these problems.…”
Section: Preventionmentioning
confidence: 99%